Kajian Filosofi dan Aktualisasi Ajaran Bhakti Yoga - Ngakan Ketut Juni; I Made Adi Brahman (Sphatika: Jurnal Teologi, 2021)
The teaching of bhakti yoga is a teaching that examines how or how to connect and unite with God. Bhakti yoga emphasizes the path of developing deep compassion, reverence, service and devotion towards God in all His manifestations. The teaching of bhakti yoga is expressed in several ways, including: carrying out prayers / worship, having a heart full of gratitude, respecting anyone, and carrying out social activities.